Implementasi Pancasila Sebagai Kunci Keberhasilan Paguyuban Kawula Keraton Surakarta Hadiningrat dalam Melestarikan Budaya Lokal di Indonesia - Marsudi, Kenlies Era Rosalina; Cahyani, Arik (Sultan Journal of Social Sciences and Humanities, 2024)
This study aims to find out and explore the implementation of Pancasila by PAKASA in preserving Ponorogo culture and to provide awareness to the public about the importance of preserving local culture, especially in Ponorogo. This research uses qualitative methods based on the results of observation, interview and documentation. Pancasila is the most basic education for every element of state life which is used as a standard and guide for life in living a good civic life in accordance with Pancasila values. With so many new cultures emerging in this era of modernization and globalization, it is hoped that people will always be able to apply the values ​​of Pancasila and Indonesian culture. And as for PAKASA's efforts in preserving the culture in Ponorogo by maintaining ethics and morals towards people's behavior to maintain Pancasila values. From the results of the collection and analysis of data and information it can be seen that: 1). PAKASA has a very important role in preserving Ponorogo culture2). Method of preparation and implementation of activities based on the implementation of Pancasila 3). The implementation of Pancasila is the key to PAKASA's success in preserving the original culture of Ponorogo.